The Influence of Brand Equity, Price and Product Quality on Purchase Decisions for iPhone Brand Mobile Phones - Arifin, Fakhira; Mustari, Mustari; Dinar, Muhammad; Nurdiana, Nurdiana; Hasan, Muhammad (Economic Education and Entrepreneurship Journal, 2023)
The purpose of this research is to see whether Brand Equity, Price, and Product Quality have partial and simultaneous effect on the Decision to Purchase Iphone Brand Mobile Phones in Minasatene Village, Pangkep Regency. This research is a quantitative descriptive study involving 50 participants. Information was collected by distributing Likert scale questionnaires. Descriptive statistical analysis and inferential statistical analysis were used to analyze the data. The results of the study reveal that the variables of Brand Equity (X1), Price (X2), and Product Quality (X3) all have a positive and significant effect on the Purchase Decision (Y) of iPhone Brand Mobile Phones in Minasatene Village, Pangkep Regency.Keywords: Brand equity, Price, Product Quality, Purchase DecisionDOI: http://dx.doi.org/10.23960/E3J/v6i1.31-41